1995
DOI: 10.2118/95-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Asessment of Solvent Extraction Efficiency In Sandstones Using BET Specific Surface Area Measurements

Abstract: Cleaning core is standard procedure prior to routine measurement of parameters such as porosity and permeability and before performing special core analyses. It is shown that the cleaning efficiency of different solvents and the degree of cleanliness of a core can be assessed through specific surface area measurement. Berea and Crossfield Cardium sandstone core plugs containing residual Crossfield Cardium oil from-laboratory core floods were extracted with the azeotropic mixture of chloroform/methanol, toluene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The specific surface area measured by N 2 -BET is 0.985 m 2 /g, which can be underestimated due to the existence of oil film in the sample (French et al, 1995). The total pore surface areas obtained from the MIP and XCT method are listed in Table 1.…”
Section: Pore Surface Areamentioning
confidence: 99%
“…The specific surface area measured by N 2 -BET is 0.985 m 2 /g, which can be underestimated due to the existence of oil film in the sample (French et al, 1995). The total pore surface areas obtained from the MIP and XCT method are listed in Table 1.…”
Section: Pore Surface Areamentioning
confidence: 99%
“…Consistent with observations in Berea sandstone (35) , a reduction in the specific surface area of the limestone from 0.24 to 0.17 m 2 /g was observed after asphaltene adsorption. Other investigators have found that the presence of small amounts of residual organic matter can lower a rock's specific surface area (39)(40)(41) .…”
Section: Asphaltene Treatment Of Indiana Limestone Coresmentioning
confidence: 99%